TDP-43 is intercellularly transmitted across axon terminals - Feiler, Marisa S.; Strobel, Benjamin; Freischmidt, Axel; Helferich, Anika Marie; Kappel, Julia; Brewer, Bryson M.; Li, Deyu; Thal, Dietmar R.; Walther, Paul; Ludolph, Albert C.; Danzer, Karin M.; Weishaupt, Jochen H. (The journal of cell biology, 2015)
Transactive response DNA-binding protein 43 kD (TDP-43) is an aggregation-prone prion-like domain-containing protein and component of pathological intracellular aggregates found in most amyotrophic lateral sclerosis (ALS) patients. TDP-43 oligomers have been postulated to be released and subsequently nucleate TDP-43 oligomerization in recipient cells, which might be the molecular correlate of the systematic symptom spreading observed during ALS progression. We developed a novel protein complementation assay allowing quantification of TDP-43 oligomers in living cells. We demonstrate the exchange of TDP-43 between cell somata and the presence of TDP-43 oligomers in microvesicles/exosomes and show that microvesicular TDP-43 is preferentially taken up by recipient cells where it exerts higher toxicity than free TDP-43. Moreover, studies using microfluidic neuronal cultures suggest both anterograde and retrograde trans-synaptic spreading of TDP-43. Finally, we demonstrate TDP-43 oligomer seeding by TDP-43-containing material derived from both cultured cells and ALS patient brain lysate. Thus, using an innovative detection technique, we provide evidence for preferentially microvesicular uptake as well as both soma-to-soma “horizontal” and bidirectional “vertical” synaptic intercellular transmission and prion-like seeding of TDP-43.
Gesehen am 16.06.2021